THE ROLE OF MUSIC IN STRESS MANAGEMENT: तनाव प्रबंधन में संगीत की भूमिका - Awasthi, Anuradha (International Journal of Research -GRANTHAALAYAH, 2015)
Stress management refers to the development of certain psychological and physiological mechanisms that can be learned to reduce the side effects of human body and mind. According to Richard Lazarus and Susan Folk Men, when a person has few resources to reach a goal and the work to be done is too much, then he gets stressed. Research by Walter Cannon and Hans Salleay found that stress has negative effects on the body and mind. It is necessary for every human being to learn the techniques of stress management in order to live a satisfying, balanced and happy life. One of these techniques is the use of music. According to Jain Collingwood, music has such unique power that it reduces stress by affecting us emotionally. The melody of music makes the human mind happy, the lyrics of the song inspire the person and the heart likes the rhythm. Music affects all humans. The tradition of singing and dancing with different instruments in different languages ​​and dialects has been found in all the societies of the world, that is, music provides universal joy. तनाव प्रबंधन का अर्थ कुछ ऐसी मनेावैज्ञानिक और शारीरिक क्रियाआंे की प्रणाली विकसित करने से है जिन्हें सीख कर मनुष्य के शरीर और मन पर पडने वाले दुष्प्रभावोें को कम किया जा सकता है। रिचर्ड लज़ारस तथा सुसैन फोक मेन के अनुसार जब मनुष्य के पास किसी लक्ष्य तक पहुंचने के लिए संसाधन कम होते है और पूरे किये जाने वाले काम बहुत अधिक होते है तो उसे तनाव होता है। वाॅल्टर कैनन तथा हैन्स सेल्ये ने मनुष्यों तथा प्राणियों पर किये गये शोध मे पाया कि तनाव शरीर और मन पर नकारात्मक प्रभाव डालता है। प्रत्येक मनुष्य के लिए यह आवश्यक है कि वह संतोषप्रद, संतुलित और सुखी जीवन जीने के लिये तनाव प्रबंधन की तकनीके सीखे। इन्हीं तकनीको मे से एक है संगीत का उपयोग। जैन कालिंगवुड के अनुसार संगीत मे एैसी अनोखी शक्ति होती है जो कि हमें भावनात्मक रूप से प्रभावित कर तनाव को कम करती है। संगीत की स्वर लहरियाँ मनुष्य के मन को आनंदित करती हैं गीत के बोल व्यक्ति को प्रेरित करते हैं तथा लय मन को अच्छी लगती है। सभी मनुष्यों को संगीत प्रभावित करता है। विश्व के सभी समाजों मंे भिन्न - भिन्न भाषाओं और बोलियों में विभिन्न वाद्यों के साथ गाने तथा नृत्य करने की परंपरा पाई गई है अर्थात् संगीत सार्वभौमिक रूप से आनन्द प्रदान करता है।